Fungicide soybean seed treatment: interactions with inoculant, soil, and plant - Sartori, Felipe Fadel (2020)
Seed treatment has become part of the soybean production in Brazil and, currently, almost a hundred percent of the areas use this type of pesticide application. Nevertheless, despite its solid commercial presence, questions regarding the interaction of pesticides with biological products and the environment arise year after year. Thus, the objectives of the present study were: (i) to determine how soybean seed treatment with fungicides associated with Bradyrhizobium elkanii pre-inoculation can be detrimental to the biological nitrogen fixation (BNF) and yield; (ii) how fungicides applied via seed treatment are absorbed and translocated in seedlings, and how they interact with the soil and its properties; (iii) and the longevity of fungicide action along plant development. In order to investigate these goals, four field and seven greenhouse experiments were carried out over the years 2016, 2017, 2018 and 2019. The field experiments aimed to evaluate the effect of fungicides plus pre-inoculation with B. elkanii on soybean seeds, both on BNF and yield, evaluating the concentration of ureides, the BNF efficiency and the productivity components of the crop. The greenhouse experiments sought to elucidate the absorption and translocation pattern of different fungicides applied via seed treatment in soybeans using radiolabels active ingredients, as well as the longevity of seed treatment efficacy on controlling Phytophthora sojae, assessing severity of root rot and plant development. The results showed that both seed treatment and pre-inoculation affect BNF, however, did not cause impacts on yield. In addition, seed treatment did not have superior yield than control with inoculant alone in any of the experiments. Regarding the absorption and translocation of fungicides applied via seed treatment in soybean, it was observed that most products, when absorbed, were concentrated in the cotyledons of plants, and that the soil organic matter content can influence the absorption of the products. Finally, regarding the longevity of action of fungicides during plant development, it was shown that the satisfactory efficacy in the management of Phytophthora sojae was up to 14 days after planting.